An efficient power conservation scheme in non-zero-sum duty-cycle game for wireless sensor networks. (2016) - Tseng, Fan-Hsun; Cho, Hsin-Hung; Chou, Li-Der; Shih, Timothy K.; Chao, Han-Chieh
Wireless sensor network (WSN) is still a popular research field, which can be applied to various emerging research topics such as internet of things and smart grid. The sensor nodes are responsible to detect the new environment and monitor the variable situation, but suffer from battery powered with energy limitation. In this paper, we define the power consumption problem in the overlapping area based on integer linear programming (ILP). Then, we propose a game-based model named non-zero-sum duty-cycle game (NZS-DCG) to express the cooperation between sensor nodes, and formulate the equilibratory equation based on Nash Equilibrium to decide the optimal strategy. The simulation results show that the cooperative scheme provides the lowest power consumption and the longest network lifetime than other related literatures. In conclusion, the power conservation and traffic relieving in WSN can be achieved by the proposed game model.